Menilik Makna Simbolik Seni Tradisi Bonet - Snae, Patce Orianus; Lenama, Hendrik; Nulik, Cici; Tadius Neken, Yuden (Universitas Sultan Ageng Tirtayasa, 2025)
Bonet is a traditional art that is inherent in the Bikekneno community as the identity of the community, which unites the community and as a form of respect for the ancestors. This study aims to analyze the symbolic meaning of the Bonet art tradition in the Bikekneno community. This study uses a qualitative research method with a semiotic approach according to Barthes through denotative and connotative meanings to describe the phenomenon of Bonet Tradition art in society and an ethnographic approach to identify social phenomena and problems in the Bikekneno Village community. The results of the study show that the Bonet tradition is carried out by the Bikekneno Village community with several stages or flows, namely the preparation stage, namely Boen Buat, Boen Bako, and Basan Bonet. At each stage in carrying out the Bonet tradition, there are signs or symbols that can be interpreted denotatively and connotatively. Bonet also has various meanings contained in it, such as a circle depicting the integrity of the Bikekneno community which is broken by various types of obstacles. Stomping feet together depicts the togetherness of the community in various conditions. Holding hands is a form of unity depicted in Bonet. The fire symbol is a form of sign or call for the community to gather in a circle of unity.